2011
DOI: 10.1038/nn.2790
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic pre-ictal discharges emerge at the transition to seizure in human epilepsy

Abstract: Mechanisms involved in the transition to an epileptic seizure remain unclear. We studied this question in tissue slices from human subjects with mesial temporal lobe epilepsies. Ictal-like discharges were induced in the subiculum by increasing excitability together with an alkalinization or low Mg 2+ . During the transition, distinct pre-ictal discharges emerged concurrently with interictal events. Intracranial recordings from the mesial temporal cortex of epileptic subjects revealed similar discharges before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
303
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 268 publications
(337 citation statements)
references
References 50 publications
27
303
1
Order By: Relevance
“…Similar results have recently been published by Huberfeld et al (2011) who studied the transition from interictal-to ictal-like epileptiform discharges in the subiculum of brain slices that were obtained from TLE patients undergoing surgery. It should be noted that in order to obtain a pattern of ictal-like activity these authors had to employ multiple pharmacological manipulations of the superfusing medium including high K + , low Mg 2+ and Ca 2+ , or external alkalinization, since a "single" manipulation consisiting of bath application of 4AP, high K + , low Mg 2+ or bicuculline failed in inducing ictal-like events.…”
Section: Initiationsupporting
confidence: 84%
See 3 more Smart Citations
“…Similar results have recently been published by Huberfeld et al (2011) who studied the transition from interictal-to ictal-like epileptiform discharges in the subiculum of brain slices that were obtained from TLE patients undergoing surgery. It should be noted that in order to obtain a pattern of ictal-like activity these authors had to employ multiple pharmacological manipulations of the superfusing medium including high K + , low Mg 2+ and Ca 2+ , or external alkalinization, since a "single" manipulation consisiting of bath application of 4AP, high K + , low Mg 2+ or bicuculline failed in inducing ictal-like events.…”
Section: Initiationsupporting
confidence: 84%
“…It should be noted that in order to obtain a pattern of ictal-like activity these authors had to employ multiple pharmacological manipulations of the superfusing medium including high K + , low Mg 2+ and Ca 2+ , or external alkalinization, since a "single" manipulation consisiting of bath application of 4AP, high K + , low Mg 2+ or bicuculline failed in inducing ictal-like events. In these experiments, Huberfeld et al (2011) found that distinct pre-ictal discharges, which emerged concurrently with interictal events, depend on glutamatergic mechanisms and are preceded by pyramidal cell firing, whereas interneuron firing precedes interictal events that depend on both glutamatergic and depolarizing GABAergic signaling; moreover, preictal spikes spread faster that interictal-like discharges suggesting a reduced inhibitory restraint.…”
Section: Initiationmentioning
confidence: 93%
See 2 more Smart Citations
“…During the progressive recruitment to a seizure, before GABAergic inhibition weakens and an ever growing excitatory drive starts to dominate the firing dynamics (Dzhala and Staley, 2003;Huberfeld et al, 2011;Jiruska et al, 2010a;Timofeev and Steriade, 2004;Trevelyan et al, 2006), there is a major contribution of synchronous GABAergic potentials to HFO in the beta (20-30 Hz) and the gamma range (40-120 Hz) (Gnatkovsky et al, 2008;Köhling et al, 2000;Trevelyan et al, 2006;Trevelyan, 2009). Later on, this rhythmic GABAergic inhibition progressively decreases driven by the collapse of chloride gradients together with a desychronization of interneuronal firing (Derchansky et al, 2008;Dzhala et al, 2010;Gnatkovsky et al, 2008;Lasztoczi et al, 2009;Timofeev et al, 2002b;Viitanen et al, 2010).…”
Section: Single Cell Dynamics During a Wide Range Of Hfo In Epileptogmentioning
confidence: 99%